Strengthening Gender Instrument and Women’s Agency: a Study of Disaster Risks in Indonesia, Philippine, and South Korea - Lestariningsih, Dian (Jurnal Perempuan, 2015)
UNDP 2004 has reported that 75% of the world inhabit a high-risk disaster-prone area. Oxfam 2005 has narrated that during the tsunami attacking Indonesia and other countries, 77% casualties were women and girls. This facts shall strengthen the understanding of international gender instrument that support those who are vulnerable during disaster. Indonesia has impotant task to work and cooperate among multistakeholders such as government, communities, CSOs, NGOs, mass medias, etc to reduce disaster-risks. Indonesia should also pay more attention to promote women’s agency in reducing disaster-risks.